What Can We Learn from EU ETS? - Herman R. J. Vollebergh; Corjan Brink (Center for Economic Studies and ifo Institute (CESifo), 2020)
This paper discusses lessons that other regions could learn from European Union's effort to implement carbon pricing through EU Emission Trading System (EU ETS). Our lessons are, first of all, that a cap-and-trade system like EU ETS is very helpful in guaranteeing a credible and binding reduction of emissions through its cap within the sectors subject to this regulation. Second, providing enough flexibility for trade, in particular intertemporal trade, is essential but should also be guided with care. The current quantity rules for the Market Stability Reserve to steer the abundancy of allowances seems a promising new feature for cap-and-trade policies, although price collars for newly designed systems create more transparency. Third, it is far from obvious why EU ETS should cover the entire carbon emissions base if other instruments, like (implicit) carbon taxes are already available. Finally, EU ETS seems at least partially responsible for the observed steady reduction of carbon emission within the EU ETS sectors. However, the gradual tendency to outsource emissions to other regions justifies carbon border adjustment mechanisms for selected sectors if other regions do not impose carbon pricing rules.
Keywords: D47; D62; Q54; Q58; 330; climate policy; carbon pricing; European Union Emission Trading System; Market Stability Reserve